2013
DOI: 10.1017/s0007114513002456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bovine lactoferrin on the immature porcine intestine

Abstract: Bioactive milk proteins may be important in protecting preterm infants from developing inflammation and necrotising enterocolitis (NEC). A preterm pig model was used to investigate the protective effects of enteral bovine lactoferrin (bLF) against NEC development and inflammation. Caesarean-delivered preterm pigs were fed parenteral and minimal enteral nutrition for the first 2 d followed by 2 d of total enteral nutrition before euthanasia. Pigs were stratified into two groups and fed with either a control for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…14 Bovine lactoferrin of 0.1-1g/L administrated to NEC piglet can stabilize hypoxia-induced factor-1a (HIF-1α) and inhibit inflammation pathways including NF-κB, TNF receptorassociated factor 6 and p38 pathways. 4 Lactoferrin administration at a high concentration (10 g/L) upregulated NF-κB pathway and activated HIF-1α, resulting in colonic lesions and reduced intestinal villus height/crypt depth ratio in the immature small intestine of piglets. 4 At 6 g/L, we detected reduced nuclear NF-κB in lactoferrin-treated NEC mice compared with NEC alone.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…14 Bovine lactoferrin of 0.1-1g/L administrated to NEC piglet can stabilize hypoxia-induced factor-1a (HIF-1α) and inhibit inflammation pathways including NF-κB, TNF receptorassociated factor 6 and p38 pathways. 4 Lactoferrin administration at a high concentration (10 g/L) upregulated NF-κB pathway and activated HIF-1α, resulting in colonic lesions and reduced intestinal villus height/crypt depth ratio in the immature small intestine of piglets. 4 At 6 g/L, we detected reduced nuclear NF-κB in lactoferrin-treated NEC mice compared with NEC alone.…”
Section: Discussionmentioning
confidence: 97%
“…Low dose (0.1-1g/L) lactoferrin can activate cell proliferation and downregulate inflammation, while a higher dose (10g/L) can be detrimental by inhibiting cell proliferation and upregulating inflammation. 4 In the present study, we used a dosage of recombinant lactoferrin (0.3 g/kg/day) at a concentration of 6 g/L, to approximate the concentration in human colostrum. We found that lactoferrin administration improved the severity of intestinal injury of experimental NEC, downregulated inflammation markers (IL-6, TNF-α, nuclear NF-kB), and significantly upregulated the expression of intestinal stem cell and proliferation markers (Lgr5, Ki67, and nuclear βcatenin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as newborn babies supplementation [24] or as a feed supplement for newborn piglets [25, 26]. Although there are several producing systems in which LF can be produced as recombinant [27, 28], bovine colostrum still remains as an important source of bioactive constituents incl.…”
Section: Introductionmentioning
confidence: 99%
“…In a neonatal rat model of NEC, bovine Lf significantly reduced NEC incidence; the protective effect was associated with increased density of mucin-producing goblet cells in the terminal ileum and changed ileal morphology (Wittke 2013). In a piglet model of NEC Lf had positive effects: increased cell proliferation via extracellular signal-regulated kinase, limited IL-8 secretion and prevented NF-kB and hypoxia-inducible factor-1a activation, suggesting strong anti-inflammatory effects (Nguyen et al 2014). …”
Section: Lactoferrin and Neonatal Infectionmentioning
confidence: 99%